Strategic Communication and Neuromarketing in the Fisheries Sector: Generating Ideas From the Territory - Russo, Vincenzo; Milani Marin, Laura E.; Fici, Alessandro; Bilucaglia, Marco; Circi, Riccardo; Rivetti, Fiamma; Bellati, Mara; Zito, Margherita (Frontiers in Communication, 2021)
Background: Globalization and technological progress has changed the relationships among fisheries, society and markets. The industrial primacy has led, among others, to the marginalization of fishermen and the deletion of local culture. It followed a loss of the conventional link between territory and traditions, with a change in consumer behaviour. Aim: The purpose of this study is to investigate the way through which the communication of territoriality of fish products influences the consumers’ quality perception, their willingness to pay and the exploration of packaging, in the Italian context. Method: In order to obtain quantitative and qualitative data on visual paths (the series of fixations and saccades) and areas of interest (AOI) of the analyzed packaging, gaze data were recorded. AOI permits to define regions of a visual stimulus and to link eye-movement measures to parts of the used stimulus. This study used AOI in order to measure Spent Time (the amount of time that consumers have spent looking at a particular AOI) and Entry Time (the time passed from the moment of the first fixation in a particular AOI) on brands and on products. Results: The results of the drivers identified crucial points for the future communication of fish products and the promotion of the territory. In particular, the analysis lays the foundations for a reorganization of the approach to the creation of product packaging, through greater attention to detail and the intrinsic values that this can express. Conclusion: The use of neuromarketing techniques has proved to be valid in identifying what is the main information that is processed for the evaluation of the product also considering the role played by emotions.